Stability and phosphorus leaching of tilapia feed in water - Bueno, Guilherme Wolff [UNESP]; Mattos, Bruno Olivetti de; Neu, Dacley Hertes; David, Fernanda Seles [UNESP]; Feiden, Aldi; Boscolo, Wilson Rogerio (Univ Federal Santa Maria, 2019)
The present research aimed to investigate the stability of pellets and phosphorus leaching of diets formulated for juveniles of Nile tilapia (Oreochromis niloticus), with different sources of phosphorus and different exposure times in water. Six diets were elaborated by varying the source of phosphorus (1 - dicalcium phosphate (DP): 2 - meat and bone meal (MBM); 3 - poultry meal (PM); 4 - anchovy meal (AM); 5 - tilapia filleting industrial meal (TM); 6 - calcined bone meal (CBM)) and, then, were submitted to four exposure times in water (5, 10, 15 and 20 minutes), with three replicates. Thus, 72 aquariums of 30-liters were used, each being an experimental unit. All diets were evaluated for electrical conductivity of water, turgidity of pellets, mineral matter leaching, flotation of pellets, and total phosphorus leaching. Only turgidity and flotation of pellets varied with the different sources of phosphorus in the diets. The MBM diet had the highest turgidity of pellets. The PM, AM, and CBM diets had the highest flotation of pellets. The total phosphorus leaching had a linear effect with the increase of the exposure tune, showing a greater release of phosphorus in the water with increase of exposure time. Data showed that PM, AM, and CBM diets had less potential impact on the aquatic environment. Conversely, the TM diet has greater polluting potential. These results showed that diets formulated with different sources of phosphorus exhibit distinct actions in the water, providing different effects on the fish culture environment.
Keywords: aquaculture; aquafeed; environmental impact; phosphorus leaching; water quality